Factors Affecting Thailand Higher Education Students’ Financial Instrument Investment - Lomtaku, Wanlop; Leewiwatwong, Sittichai (Rajapark Journal, 2024)
The purpose of this study was to examine the factors that affect Thai higher education students’ financial instrument investment. The study was quantitative research. The data were analyzed using mean, standard deviation, and logistic regression analysis. The research findings are as follows: First, most of the university students who answered the questionnaire do not have an investment. They are female, study social science, and have an average monthly income of equal to or less than 5,000 baht. Their average monthly investment is also equal to, or less than, 5,000 baht. Second The students who had invested and those who did not, were significantly different in the level of financial knowledge, ability to take risk, willingness to take risk, investment personality, and expected return. Finally, the model of factors affecting Thailand higher education students’ financial instrument investment was suitable, and the accuracy of the model to predict Thailand higher education students’ financial instrument investment was 69.60%. Moreover, there were three factors that significantly affected Thai higher education students’ financial instrument investment: average monthly investment, ability to take risk and willingness to take risk, and financial knowledge.